Productivity Growth, Technological Convergence, RandD, Trade, and Labor Markets : Evidence From the French Manufacturing Sector - Khan, Tehmina S. (IMF Working Papers; Working Paper, 2006)
Total factor productivity (TFP) of 14 manufacturing sectors in France has kept up with that of the United States during 1980-2002 and remained well above that of the United Kingdom. Estimates using a dynamic panel equilibrium correction model indicate that sectors further behind the technological frontier experience faster productivity growth and that spending on research and development and trade with technologically advanced economies positively influences TFP growth, but not the speed of convergence. Conversely, TFP growth is negatively related to some key labor market variables, namely the replacement ratio and the ratio of the minimum wage to the median wage.